PENGARUH POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIOANL ANAK USIA 4-6 TAHUN DI TKK SATU ATAP LEBIJAGA - Mude, Skolastika; Meka, Marsianus; Juita, Angelina Kurnia; Nafsia, Andi (Bunayya, 2026)
Social-emotional development in children aged 4–6 years is a crucial aspect that plays a role in their ability to interact with others, manage their emotions, and adapt to their social environment. Based on initial observations at the One-Stop Kindergarten (TKK Satu Atap) in Lebijaga, it was found that some children still experience difficulties in controlling their emotions, cooperating with peers, and complying with classroom rules. This study aims to determine the relationship between parenting styles and the social-emotional development of children aged 4–6 years. This study used a quantitative approach with a correlational design. The sample consisted of 19 children and parents, selected using a total sampling technique. Parenting style variables included authoritarian, permissive, and democratic parenting styles, while children’s social-emotional development was measured using indicators of emotional regulation, empathy, cooperation, and independence. Data were collected using questionnaires and supported by observations. Data were analyzed using the Pearson Product-Moment correlation test using SPSS. The analysis showed that the relationship between parenting styles and children’s social-emotional development was very low and did not demonstrate statistical significance. The correlation values ​​obtained were authoritarian parenting (r = 0.162; p = 0.508), permissive parenting (r = 0.100; p = 0.684), and democratic parenting (r = 0.086; p = 0.725), with a significance value greater than 0.05. These findings indicate that the social emotional development of children in this study may be influenced by other factors, such as the school environment, interactions with peers, and the role of teachers in the learning process.